Transforming Agricultural Supply Chain with Advanced Technologies - Patro, Ravindra Kumar; Choudhury, Shayan Roy; Patro, Janaki Prasad (International Journal of Supply Chain Management, 2024)
In a time of unprecedented technological advancement and increasing globalization, the complexities of Global Agricultural Supply Chains (GASC) are becoming more intense. This research paper explores the intricate interplay between advanced technologies, globalization forces, and the multifaceted challenges faced by GASC. By using a multidisciplinary approach that includes historical analysis, in- depth case studies, and speculative scenarios, this research uncovers important insights into how technology adoption, trade dynamics, and geopolitical events shape the resilience and sustainability of GASC. The findings show a positive link between technology adoption and agricultural productivity, while also highlighting concerns about job displacement and the digital divide. Additionally, the research emphasizes the importance of trade diversification and strong risk management strategies in mitigating disruptions caused by geopolitical instability. By providing practical recommendations for businesses, policymakers, and academics, this research contributes to a deeper understanding of how to navigate the complexities of GASC in an ever-changing global landscape.